Analisa Faktor Internal dan Perencanaan Operasional PT Nuno Care Post Partum Depression Pusat Perawatan Pasca Melahirkan - Novika Dwi Anggraini; Dimas Angga Negoro; Unggul Kustiawan; Mohamad Reza Hilmy (Yayasan Literasi Sains Indonesia, 2025)
This study aims to identify and analyze internal factors that influence operational planning at PT Nuno Care, a postpartum care center with a focus on handling postpartum depression, understand the role of human resources, facilities, management processes, and technological capabilities in improving the effectiveness and efficiency of operational services. To develop strategic recommendations for PT Nuno Care management to improve service quality, operational effectiveness, and business sustainability of the postpartum care center. Using a qualitative descriptive approach, data were collected through literature studies, interviews with staff and management, and direct observation in the center's operations. The results of the analysis revealed that human resource factors, facility availability, management processes, and technological capabilities are crucial aspects that influence the effectiveness of operational planning. This study provides strategic recommendations for improving service quality and operational efficiency that can support the success of PT Nuno Care in providing optimal postpartum care. Nuno Birth makes services easier by creating an application that is integrated with payment systems, registration, communities and patient history checking.